Lack of biochemical signalling in GelMA leads to polarity reversion in intestinal organoids independent from mechanoreciprocity - Lenie Vanhove; Thomas Van Gansbeke; Bert Devriendt; Ruben Van der Meeren; Ruslan I. Dmitriev; Irina A. Okkelman (Journal of Tissue Engineering)
Xenogeneic tumour origin and batch-to-batch variability of Engelbreth-Holm-Swarm sarcoma tumour cell-derived hydrogels (Matrigel, Cultrex) limit the biomedical application of organoids in tissue engineering. The gelatin-methacryloyl (GelMA) hydrogels represent a defined, tunable, and GMP-friendly alternative, but they are rarely studied as alternative to Matrigel. Here, we studied effects of mechanical properties of GelMA and addition of laminin-111 on encapsulation and growth of small intestinal organoids. GelMA-embedded organoids displayed polarity reversion, resulting in apical-out and apical-basal phenotypes, independent from the matrix stiffness. Addition of laminin-111 softened hydrogels and also resulted in a partial restoration of the basal-out phenotype. Interestingly, despite the incomplete polarity restoration, GelMA-organoids still showed minor growth. GelMA stiffness and concentration influenced the transition from 3D to 2D organoid cultures. Collectively, our study confirms that tuning of GelMA mechanical properties alone cannot recapitulate the basal membrane matrix. However, controlled polarity reversion offers a tool for engineering organoids and enabling apical membrane access.